Managing Collective Processes in the Creative Industries: Insight from Perfumery and Haute Cuisine. Issue 1 (7th October 2015) - Paris, Thomas; Lang, Gerald
<x xml:space="preserve">Abstract</x> Despite growing interest in the managerial and organizational dimensions of creative industries, little research has focused on the collective aspect of the creativity processes that underlie them. A study of the creative processes in perfumery and haute cuisine finds that creativity in those sectors is not the province of a gifted individual but, rather, the outcome of a collective process. The findings lead to a four‐stage model of the creative process—inspiration, framing, formulation, and validation—that can be used to both enhance creativity in the workplace and avoid some of the problems associated with the management of individuals in creative enterprises. © 2015 Wiley Periodicals, Inc.